The Influence of Parents on Medication Adherence of Their Children in China: A Cross-Sectional Online Investigation Based on Health Belief Model - Ge, Pu; Liu, Si-tong; Xu, Shu-xian; Zhang, Jin-zi; Lai, Yong-jie; Fu, Run-chen; Ke, Xin-yu; Zhao, Juan; Bian, Ying; Wu, Yi-bo (Frontiers in Public Health, 2022)
Objective: To explore the influence of parents on medication adherence of their children. Study design: A cross-sectional online investigation. Methods: A questionnaire with 41 questions was designed based on health belief model (HBM) which was distributed and collected online in 28 cities around China through multi-stage stratified sampling. The reliability of the questionnaire was assessed with Cronbach's α coefficient and split-half reliability, and its validity was evaluated with exploratory factor analysis and content validity index. The structural equation model (SEM) was constructed to explore the relationship between the parents' health belief and their children's medication adherence. Subgroup analysis was conducted to study the differences between parents with different demographic characteristics (male and female, rural and urban). Results: A total of 573 questionnaires were included for analysis, with an effective rate of 62.97%.The Cronbach’α coefficient of the questionnaire was 0.821＞0.6, the split-half reliability was 0.651＞0.6, the I-CVI of each dimension were greater than 0.78, and the S-CVI/AVE (I-CVI average) was 0.95＞0.9. The result of the questionnaire exploratory factor analysis met the standard. According to the SEM, self-efficacy (=0.177), perceived susceptibility (=-0.244), and perceived severity (=0.243) were direct influencing factors of children’s medication adherence. In the subgroup analysis, the model established by each subgroup was basically consistent with the model established by the overall sample. The absolute values of females' perceived susceptibility, perceived severity, and self-efficacy for their children's medication adherence path coefficients were higher than those of males. Conclusion: Parents' perceived severity and self-efficacy may have a positive direct impact on their children's medication adherence, while parents’ susceptibility to children’s medication non-adherence may have a negative direct impact on children’s medication adherence. Objective constraints, perceived barriers, perceived benefits may have an indirect impact on children's medication adherence. Women's health belief appear to have a greater impact on their children's medication adherence than men. It may be an effective strategy to increase their children's medication adherence by improving parents' health belief.